Inclusiveness and Social Justice in Evaluation: Can the Transformative Agenda Really Alter the Status Quo? A Conversation with Donna M. Mertens - Michele Tarsilla (The Evaluation Center at Western Michigan University, 2010)
Background: Evaluation is sometimes viewed as a professional practice rather than a discipline corresponding to a well defined set of theories. However, Shadish, Cook and Leviton (1991) were able to demonstrate that evaluators' work does have theoretical foundations. In particular, the authors identified five main elements for evaluation theory and described the contribution made to each of them by seven of the most influential scholars in the field over the last five decades.   Purpose: This paper intends to further the discussion on evaluation theory, by examining some of the contributions made by Donna Mertens. The main focus of the paper is on her innovative ideas on each of the five main elements of evaluation theory.   Setting: Not applicable.   Subjects: Not applicable.   Research Design: Not applicable.   Data Collection and Analysis: The paper is the result of both a desk review of her work on transformative evaluation, inclusiveness, and social justice, and a phone interview with her. For the sake of accuracy, the text of the interview and the corresponding analysis were submitted to Mertens for review prior to publication. Findings: The author demonstrates how Mertens has incorporated the five principles into her own work and practice. According to Mertens, evaluators need first to be cognizant of the plurality of values held by the communities where they work and second to let those very same values guide the design, implementation, and use of evaluation. Based on her belief that knowledge is not neutral but is influenced by human interests, Mertens calls upon evaluators to play a more active role in the construction of new and "socially compensatory" knowledge. In doing so, Mertens particularly stresses how evaluation practice could address and challenge the social, cultural and economic inequities perpetuated by the status quo.   Conclusions: Pursuing inclusiveness and social justice in evaluation is possible. Transformative evaluation is capable of altering the status quo. Transformative evaluation is instrumental in bringing about not only social change but also social transformation. This article also shows that the debate on evaluation's main theoretical foundations is still relevant. Such theoretical categories are especially beneficial in that provide common ground for understanding.   Keywords: transformative evaluation, social justice, cultural competence, inclusiveness, valuing, social programming, knowledge, practice, use